A single spark [large type] - Miller, Judith, 1944- (Thorndike Press large print Christian fiction, 2020)
"Wanting to do her part in the Civil War effort, Clara McBride goes to work at the Washington Arsenal. Lieutenant Joseph Brady is drawn to Clara but must focus on preventing explosions in the factory. When shipments of cartridges fail to fire and everyone is suspect, their feelings may not survive" --!cProvided by publisher.